Arteries in clinical hypertension - Safar Michael E. (Philadelphia Lippincott-Raven, 1996)
This text stresses the importance of obtaining a blood pressure reduction while also improving the structural and functional abnormalities of the large arterial vessels. The book concludes with a critical review of the therapeutic trials of hypertension.
Keywords: Hypertension -- Pathophysiology; Arteries -- Pathophysiology; Hypertension -- physiopathology